Quantitative methods for assessing a synergistic or potentiated genotoxic response - Piegorsch, Walter W.; Margolin, Barry H. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1989)
The problem of assessing chemical interactions in studies of genotoxicity is discussed. Attention is focused on assessing possible synergism or potentiation when the observed genotoxic response is binary (yes-no). Different forms of enhancement are distinguished based upon different assumptions on the genotoxic activity of the experimental treatments. A generalized linear statistical model is considered that links the probability of the binary response to the doses, and data-analytic strategies are described for detecting synergy and potentiation in factorially designed experiments. This approach is illustrated with a series of analyses of various genotoxicity data-sets.